Lone atrial fibrillation as a positive predictor of left atrial volume reduction following ablation of atrial fibrillation. Issue 1 (5th June 2013) - Fredersdorf, Sabine; Ücer, Ekrem; Jungbauer, Carsten; Dornia, Christian; Eglmeier, Julia; Eissnert, Christoph; Hamer, Okka W.; Weber, Stefan; Arzt, Michael; von Bary, Christian
Abstract: Aims: We investigated predictors of left atrial volume reduction (LAVR) in patients with atrial fibrillation (AF) undergoing AF ablation. Methods and results: Sixty patients with AF underwent pulmonary vein isolation (PVI) using a pulmonary vein ablation catheter (PVAC). All patients underwent cardiac imaging by computed tomography or magnetic resonance imaging to determine LAV 1 day before and 140 ± 9.5 days after PVI. Clinical follow-up and 72 h electrocardiogram Holter monitoring were performed 1, 3, and 6 months after ablation, and every 6 months thereafter. Significant LAVR ( n = 60, 89.3 ± 3.9 vs. 79.5 ± 3.6 mL, P < 0.0001) was shown for the study group as a whole, caused particularly by the subgroup of patients with ablation success ( n = 45, 85.2 ± 4.6 vs. 72.5 ± 3.7 mL, P < 0.0001). In addition, significant LAVR was shown for patients with lone AF ( n = 25, 88.8 ± 6.8 vs. 72.7 ± 5.3 mL, P < 0.0001), but not for patients with AF and concomitant arterial hypertension ( n = 32, 89 ± 4.8 vs. 86.7 ± 5 mL, P = 0.3), coronary artery disease ( n = 12, 91.6 ± 7.8 vs. 89.1 ± 7.8 mL, P = 0.26), or left ventricular hypertrophy ( n = 10, 86.3 ± 5.5 vs. 83.1 ± 5.3 mL, P = 0.27). Multivariate analysis revealed absence of arterial hypertension, lone AF, ablation success, and initial LA enlargement as independent predictors for significant LAVR following ablation (each P < 0.05). Conclusion: Based on the subgroup of patients with lone AF, PVI leads to a significant LAVR 4 months after the procedure, especially in patients with clinical success in terms of AF freedom. Comorbidities such as arterial hypertension may prevent this reverse atrial remodelling, despite AF freedom. Clinical implications need to be further elucidated.